1996
DOI: 10.1021/bi9513719
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Core Fucosylation on the Flexibility of a Biantennary N-Linked Oligosaccharide

Abstract: Fluorescence energy transfer was used to study the conformation of each antenna of a complex biantennary oligosaccharide. A core fucosylated biantennary oligosaccharide was converted to a glycosylamine which allowed coupling of a naphthyl donor fluorophore directly to the reducing-end GlcNAc 1. After generating an aldehyde at C-6 of residue 6 or 6' using galactose oxidase, a dansyl ethylenediamine acceptor fluorophore was coupled to either antenna of the oligosaccharide resulting in two donor-acceptor pairs. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 27 publications
0
47
0
1
Order By: Relevance
“…There are a few possible explanations of why the antibodies with nonfucosylated oligosaccharides give rise to stronger binding to Fc␥RIIIa than those in which the glycoforms are absent. A core Fuc has been shown to influence the conformational flexibility of biantennary oligosaccharides (26,27). The oligosaccharides of IgG appear to be largely sequestered between the CH2 domains and may help to stabilize the CH2 domain (28).…”
Section: Discussionmentioning
confidence: 99%
“…There are a few possible explanations of why the antibodies with nonfucosylated oligosaccharides give rise to stronger binding to Fc␥RIIIa than those in which the glycoforms are absent. A core Fuc has been shown to influence the conformational flexibility of biantennary oligosaccharides (26,27). The oligosaccharides of IgG appear to be largely sequestered between the CH2 domains and may help to stabilize the CH2 domain (28).…”
Section: Discussionmentioning
confidence: 99%
“…This suppression could, however, be due to the altered function of ␣5␤1 integrin by concomitant modification of the N-glycans. Addition of an ␣1,6fucose residue to an N-linked oligosaccharide induces an extended conformation in the oligosaccharide (Stubbs et al, 1996). Therefore, it appears that the large conformational change which occurs as a result of ␣1,6fucosylation affects the progression of malignant tumors through modification of the structure and, hence, the functions of these glycoproteins; thus, the elevated expression of ␣1,6FucT may be involved in the potential for malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that addition of an ␣1,6fucose residue to the innermost GlcNAc of the N-linked oligosaccharide leads to an unusual extended conformation (Stubbs et al, 1996). Therefore, it is possible that ␣1,6fucosylation leads to modifications of the functions of glycoproteins, such as growth factor receptors, adhesion molecules and extracellular matrices, by inducing conformational changes in the N-glycan structure.…”
mentioning
confidence: 99%
“…The currently accepted view is that chemical modification changes binding, by way of either switching the major conformation from one to another or inducing a unique bioactive conformation, rather than by making an additional unique binding site. Past studies, including NMR-based-analysis of model oligosaccharides (Homans et al 1987a), FRET experiments (Stubbs et al 1996), and molecular modeling followed by systematic bioassays with neoglycoproteins carrying synthetic biantennary N-glycans (André et al 2009), indicate a switch-like change in the shape of the glycans upon chemical modification. Figures 3 and 4 show the results of REMD simulations of four N-glycans with and without chemical modification (Nishima et al 2012).…”
Section: Modulation Of Conformational Variety By Chemical Modificatiomentioning
confidence: 99%